Constructing Control Charts, for Monitoring Chemical Parameters of Water in Kanisard Factory in Sulaimani City - Kawa M. Jamal Rashid; Gulshan Star Muhammad (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
Monitoring of the production process is an important subject for developing the quality of the product and reducing the costs, (ARIMA) residual chart is a special control chart used to specify and detect the quality behavior in time-correlated process data, to determine if they are out of control or in control. Furthermore, this type of chart is useful for adjusting and specifying the quality limits during the process. Water quality is considered the main factor of controlling human health in disease therefore, it is necessary to keep the quality of drinking water to be in control. The main objective of this study is to monitor the two important chemical parameters of drinking water which are Power of Hydrogen (PH) and Magnesium (MG), it also aims to determining the control limits for both (PH &MG) from the optimal tolerance limits to control the water production for reach better quality products in the future, by taking the data for each of the parameters (PH& MG) from January to September (2018) from the (KANISARD) factory for producing drinking water at Sulaimani city in Kurdistan region in Iraq. By using the autoregressive integrated moving average (ARIMA) control chart. The result of the study showed that both (PH &MG) processes are in statistical control by using ARIMA control chart, and also the optimal tolerance limits were determined for both of the parameters.